Do platform-Mediated workers perform better after a private digital badge is awarded? - Cristian Ramírez; Edgar E. Kausel (Computers in Human Behavior Reports, 2025)
This study examines the impact of private digital badges—visible only to recipients—on task performance in platform-mediated gig work. We conducted an experiment with 279 participants who completed an information extraction task under four conditions: private digital badges, performance feedback, monetary incentives, and a control. Private digital badges significantly improved task performance, particularly speed. Although all interventions initially slowed participants as they processed the new information, those who received badges showed the most consistent performance gains. These effects persisted even in an optional round where no further badges were awarded. In contrast, monetary incentives reduced accuracy in both rounds. These findings suggest that private badges can enhance performance by fostering competence rather than relying on social recognition, which has been the focus of most prior research on badges and awards. The study contributes new evidence on how private, non-financial incentives can improve worker performance in digital labor platforms.